Pengaruh Minat Dan Motivasi Terhadap Pemahaman Matematika Siswa Kelas X SMA Negeri 1 Dolok Batu Nanggar - Sinambela, Debora; KMA Fauzi; Kartono (Universitas Asahan, 2026)
This study examines the effects of learning interest (X1) and learning motivation (X2) on students’ mathematical understanding ability (Y) among Grade 10 students at SMA Negeri 1 Dolok Batu Nanggar in the 2024/2025 academic year. A quantitative approach was employed with a sample of 52 students selected through proportional random sampling. Data on interest and motivation were collected using questionnaires, while mathematical understanding was measured using an essay-type test. Data were analyzed using multiple linear regression with SPSS 21, preceded by assumption testing. The Kolmogorov–Smirnov test indicated that all variables were normally distributed (interest Sig. = .207; motivation Sig. = .517; understanding Sig. = .358; all > .05). Regression results showed that interest had a positive and significant effect on mathematical understanding (β = .799, t = 9.397, p < .001), and motivation also had a positive and significant effect (β = .601, t = 5.320, p < .001). Simultaneously, interest and motivation significantly predicted mathematical understanding (F = 60.156, p < .001) with R² = .711, indicating that 71.1% of the variance in mathematical understanding was explained by the two predictors. In the multiple regression model, interest was the more dominant predictor compared to motivation (βinterest = .663 > βmotivation = .301). These findings highlight the importance of strengthening students’ learning interest and motivation to improve mathematical understanding.